PENGINGKARAN HAK MASYARAKAT ADAT ATAS TANAH ULAYAT OLEH KEBIJAKAN KEHUTANAN - Widihastuti, Setiati (Universitas Negeri Yogyakarta, 2008)
Forest is the part of customary system of the tribe society. However, the forest management done by them is not facilitated in the forestry policy. The centralistic forestry policy causes the overlapping conception of the tribe forest to the state forest. While it formal normative aspect causes the acces of the tribes to the forest closed and causes reduction of wisdom-based supervision conducted by them. In fact, the community wisdom-based supervision in the socio-culture potential needing a revitalization and development as the new basis of the change of natural resources management policy which is recently controlled by the goverment proved to be the cause of law and economy harassment to the tribes society of Indonesia. Now we need to change the perception about the forest natural recource management policy controlled only by the government of the forestry instances. It should be the policy based on the community and its development principles to realize the regulation of the forest natural resources consumption. Therefore, the area division is needed to overcome the problems.